Bagaimana Work-life Balance dan Pengalaman Kerja Mempengaruhi Komitmen Organisasi? (Studi pada Perusahaan Efisiensi dan Konversi Energi di Indonesia) - Berlina Hidayati (Nomicpedia: Journal of Economics and Business Innovation, 2022)
This study aimed to analyze the effect of Work-life Balance and Organizational Experience on Organizational Commitment, where in theory these two things have contributed to the ownership of organizational commitment held by employees. This research was conducted at CV. Samaco uses a saturated sample, where the number of samples used in this study is 50 employees. The data collection method in this research uses a questionnaire that is distributed online via the Google form link. Furthermore, the analysis of this study uses multiple linear regression analysis with the help of the SPSS 24 analysis tool. Based on the results of the hypothesis testing, they show that Work-life Balance and Organizational Experience affect Organizational Commitment either partially or simultaneously. This indicates that Work-life Balance and Organizational Experience in energy efficiency and conversion company significantly influence employee commitment to the company where they work.